2021
DOI: 10.1016/j.jeurceramsoc.2020.08.031
|View full text |Cite
|
Sign up to set email alerts
|

Additively manufactured ultra-low sintering temperature, low loss Ag2Mo2O7 ceramic substrates

Abstract: This is a repository copy of Additively manufactured ultra-low sintering temperature, low loss Ag2Mo2O7 ceramic substrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 38 publications
(43 reference statements)
0
10
0
Order By: Relevance
“…With DIW, it has been shown that processing materials with an r f of ~35 and a tan d of <0.0001 can be achieved [11]. This process can also print with metal slurries alongside ceramics [12], [13], though the thermal expansion coefficients of the two materials need to be matched; otherwise, the green body will warp or crack during sintering. Out of the processes mentioned in this review, ceramics printed with DIW generally deliver the lowest-loss, highest-permittivity materials, with the capability of processing metals close to their bulk conductivity value in the same printed part.…”
Section: D Printing With Ceramics Slurriesmentioning
confidence: 99%
See 1 more Smart Citation
“…With DIW, it has been shown that processing materials with an r f of ~35 and a tan d of <0.0001 can be achieved [11]. This process can also print with metal slurries alongside ceramics [12], [13], though the thermal expansion coefficients of the two materials need to be matched; otherwise, the green body will warp or crack during sintering. Out of the processes mentioned in this review, ceramics printed with DIW generally deliver the lowest-loss, highest-permittivity materials, with the capability of processing metals close to their bulk conductivity value in the same printed part.…”
Section: D Printing With Ceramics Slurriesmentioning
confidence: 99%
“…Through process such as DIW, ceramics and metals can be printed together in the same component; however, this is a growing research area that faces considerable challenges of material compatibility and component warping due to unmatched thermal expansion coefficients. Current works demonstrate the potential of transmission lines and ring resonators printed on high-permittivity ceramics [13] in addition to miniaturized patch antennas by fully embedding the resonating patch in the ceramic [12]; an example is given in Figure 7.…”
Section: D Printed Ceramic Componentsmentioning
confidence: 99%
“…19,20 Ag 2 Mo 2 O 7 as a visible light active photocatalyst has many potential advantages (such as higher retention capacity and superior rate capability). [21][22][23][24][25][26][27] ZnS and Ag 2 Mo 2 O 7 have a suitable CB and VB positional relationship, and then they are coupled into an S-scheme heterojunction semiconductor group. For photocatalytic design, the S-scheme heterojunction is a perfect structure, promoting the disconnection of non-equilibrium carriers and maintaining the semiconductor group's power reduction and oxidation ability.…”
Section: Introductionmentioning
confidence: 99%
“…Additive manufacturing (AM) has been acknowledged as a promising enabler in manufacturing of ceramic components [17,18]. AM and its associated processes, can repeatably produce parts with performance comparable to the ones made via conventional processing, together with a greater design freedom that can deliver topologically optimised structures, functionally graded properties [19] and also multi-material printing [20,21] for producing intergraded circuitry and functional devices 3 [22]. However, there are very few examples in the literature, where AM of LTCCs for MW applications is being reported.…”
Section: Introductionmentioning
confidence: 99%
“…Printed and dried samples achieved εr = 4.4 and tanδ = 0.0006. The authors have recently demonstrated the additive manufacture of Ag2Mo2O7, an ultra-low sintering temperature and low loss MW ceramic compound, using the DIW technique [20]. Measurements from printed and fired test samples marked εr = 13.45, tanδ = 0.0005, Qxf = 17.056 and τf = -121 ppm/°C.…”
Section: Introductionmentioning
confidence: 99%